USING OF THE WEBQUESTS IN LEARNING GERMAN IN HIGHER EDUCATION ESTABLISHMENTS - Larysa O. Fedorenko (Інформаційні технології і засоби навчання, 2019)
The article highlights and describes the use of the webquests for Web 2.0 services in foreign language learning. The main stages of the work on the webquests are analyzed: the introduction of the topic, the setting of the task, the presentation of auxiliary materials, the assignment, the presentation, discussion and evaluation of the presentations. The main qualities of the service are identified: accessibility, ease of use, the possibility of communication and cooperation, including distance learning, the use of collective "mind", the possibility of creating and preserving information, visualizing the educational content, creating conditions for self-education and self-development of students. The research is based on the concepts, approaches, principles and methods of the neurodidactics. The article points out that the rational use of the webquests, as well as other Web 2.0 resources, in foreign language classes fully corresponds to the modern principles of the neurodidactics in the course of the effectiveness of the educational process, in particular: the use of the webquests contributes to increasing the motivation and intensification of learning a foreign language; gives attention to the employment of innovative characteristics, communicative activity, as well as creativity, cognitive and playful character; effectively supports the work of the teacher, promotes effective independent and group work; corresponds to the principles of "multi-channel" training; helps to eliminate language and psychological "barriers"; most often accompanied by positive emotions and indicators of academic success, which are prerequisites for motivation and effective communication in the classroom of a foreign language. The use of the webquests also corresponds to the principle of Learning by Doing, according to which our brain functions in such a way that we most effectively perceive and remember the information material that we process or develop.